Constructing the Meaning of Environmental Communication in Bagan Kuala's Marine Debris Crisis - Zuhdi, Abdurrahman; Mustofa, Basri; Samudra, Muhammad Ilham; Mandasari, Erika; Nafis, Muhammad; Nazhim Harahap, Tuongku Muhammad (UMSU, 2025)
AbstractThis study analyzes the construction of meaning in environmental communication within the marine debris crisis in Bagan Kuala Village, Serdang Bedagai Regency. The novelty of this research lies in its emphasis on the role of the family as the primary agent for instilling ecological values, moving beyond the structural approaches that have thus far been dominant. Using a qualitative case study method through participatory observation, in-depth interviews, and documentation, four main findings were identified: public misconceptions that waste in rivers strengthens the soil and that waste in the sea will disappear on its own; environmental communication that is merely ceremonial and unsustainable; differential meanings of waste among social groups; and community behavioral patterns reliant on external initiatives (dependency model). The study concludes that environmental communication strategies need to be directed into participatory and sustainable programs, with the family as the foundation for building independent ecological awareness. Keywords: environmental communication, family, marine debris, dependency behavior, ecological awareness